Desenvolvimento de antena impressa circular para microondas com aplica??es em sistemas que operam em grandes larguras de faixa - Dias, Ricardo Ant?nio (2017)
This paper aims to describe the development of a circular microstrip antenna. From a classical literature structure, an initial antenna is designed and simulated in computer environment through Ansys HFSS? program, then was inserted modifica-tions to the original design in order to obtain improvements in operating bandwidths, noting as parameter the input impedances matches for frequencies between 2GHz and 20GHz. After the initial stages of analytical calculations and computer simulations, achieving the desired goal, the substrate of interest, in this case glass fiber, Flame Retardant ? 4 (FR4), was characterized using the waveguides materials characteriza-tion technique. Obtained values of the electrical characteristics of the analyzed sub-strate, these gives the feedback computer simulations generating optimizations, so that obtained results from experimental characterization of the manufactured proto-types behave concurrently with the simulations performed.